2004
DOI: 10.18195/issn.0312-3162.22(2).2004.081-090
|View full text |Cite
|
Sign up to set email alerts
|

The benthic invertebrate fauna of the Peel-Harvey Estuary of southwestern Australia after completion of the Dawesville Channel

Abstract: -During the 1970's the Peel-Harvey Estuary experienced severe symptoms of nutrient enrichment. There were large inputs of nutrients to the system, and only limited oceanic flushing occurred, via the long, narrow Mandurah Entrance Channel. In 1994 the Dawesville Channel was constructed to increase oceanic flushing within the Peel-Harvey Estuary; reduce the occurrence of toxic phytoplankton blooms (eg. blue-green Nodularia spumzgena) and decrease macroalgal growth. The present paper compares the benthic inverteb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The sediments of the Coorong Lagoons have an abundance of bivalves, particularly A. helmsi (Chamberlayne, 2015), offering potential for reconstruction of past environmental change relevant to contemporary issues. Common in southern Australian estuaries (Matthews & Constable, 2004; Whisson et al., 2004; Lautenschlager et al., 2014), A. helmsi is an aragonitic micromollusc (Chamberlayne et al., 2020) that experiences continuous growth over a short lifespan of up to 1 year (Chamberlayne et al., 2020; Wells & Threlfall, 1982b). A monitoring study in a Western Australian estuary reported broad salinity (15–55) and temperature tolerances (18–32°C; Wells & Threlfall, 1982a).…”
Section: Introductionmentioning
confidence: 99%
“…The sediments of the Coorong Lagoons have an abundance of bivalves, particularly A. helmsi (Chamberlayne, 2015), offering potential for reconstruction of past environmental change relevant to contemporary issues. Common in southern Australian estuaries (Matthews & Constable, 2004; Whisson et al., 2004; Lautenschlager et al., 2014), A. helmsi is an aragonitic micromollusc (Chamberlayne et al., 2020) that experiences continuous growth over a short lifespan of up to 1 year (Chamberlayne et al., 2020; Wells & Threlfall, 1982b). A monitoring study in a Western Australian estuary reported broad salinity (15–55) and temperature tolerances (18–32°C; Wells & Threlfall, 1982a).…”
Section: Introductionmentioning
confidence: 99%